Chemical Composition and Insulin-Resistance Activity of Arginine-Loaded American Cranberry (Vaccinium macrocarpon Aiton, Ericaceae) Leaf Extracts - Oleh Koshovyi; Inna Vlasova; Heleriin Laur; Ganna Kravchenko; Oksana Krasilnikova; Sebastian Granica; Jakub P. Piwowarski; Jyrki Heinämäki; Ain Raal (MDPI AG, 2023)
One of the key pathogenetic links in type 2 diabetes mellitus (T2DM) is the formation of insulin resistance (IR). Besides a wide selection of synthetic antidiabetic drugs, various plant-origin extracts are also available to support the treatment of T2DM. This study aimed to investigate and gain knowledge of the chemical composition and potential IR correction effect of American cranberry (Vaccinium macrocarpon Aiton) leaf extracts and formulate novel 3D-printed oral dosage forms for such extracts. The bioactivity and IR of L-arginine-loaded cranberry leaf extracts were studied in vivo in rats. The cranberry leaf extracts consisted of quinic, 3-caffeoylquinic (chlorogenic), p-coumaroylquinic acids, quercetin 3-O-galactoside, quercetin-3-O-glucoside, quercetin-3-xyloside, quercetin-3-O-arabino pyranoside, quercetin-3-O-arabinofuranoside, quercetin 3-O-rhamnoside, and quercetin-O-p-coumaroyl hexoside-2 identified by HPLC. In vivo studies with rats showed that the oral administration of the cranberry leaf extracts had a positive effect on insulin sensitivity coefficients under the insulin tolerance test and affected homeostasis model assessment IR levels and liver lipid content with experimental IR. A novel 3D-printed immediate-release dosage form was developed for the oral administration of cranberry leaf extracts using polyethylene oxide as a carrier gel in semi-solid extrusion 3D printing. In conclusion, American cranberry leaf extracts loaded with L-arginine could find uses in preventing health issues associated with IR.